Code-Switching and Code-Mixing in Maudy Ayunda's ‎Instagram Posts: A Sociolinguistic Analysis - Putjah Aisyah Fadhillah; Ali Akbarjono (Yayasan Darussalam Bengkulu, 2023)
This study aims to analyze the forms of code-switching and code-mixing in Maudy Ayunda’s Instagram captions, focusing on the interplay between Indonesian and English. Using a qualitative descriptive approach, data was collected from Instagram posts between March 31 and December 29, 2022. Observational and documentation techniques, including screenshots of captions, were employed to gather data. The analysis reveals that Maudy Ayunda employs both code-switching (switching between languages within sentences) and code-mixing (inserting foreign words or phrases within a sentence). These practices are influenced by socio-situational factors, including her educational background and the desire to reach a broader audience. The findings suggest that Maudy Ayunda’s strategic use of language helps enhance the clarity and engagement of her posts, making her content more accessible to diverse followers. This study contributes to the understanding of language dynamics in digital communication, highlighting the role of multilingualism in online interactions.